A Cross-sectional Study of EEC Trade with the Association of African Countries - Aitken, Norman D.; Obutelewicz, Robert S. (The Review of Economics and Statistics, 1976)
Norman D. Aitken, Robert S. Obutelewicz, A Cross-sectional Study of EEC Trade with the Association of African Countries, The Review of Economics and Statistics, Vol. 58, No. 4 (Nov., 1976), pp. 425-433